Strengthening Religious Moderation in Islamic Education Learning in the Digital Era - Sahri; Aziz, Suudin (Institut Darul Falah Bandung Barat, 2025)
This research aims to analyze teachers' strategies in strengthening the values of religious moderation in PAI learning through the use of digital media, as well as to identify the challenges and their impacts on students' religious attitudes. This study employs a qualitative approach with a case study method. Data collection techniques include observing teaching and learning activities, conducting in-depth interviews with fifth and sixth-grade teachers and students, and documenting teaching materials and digital learning media. Data analysis is conducted descriptively through the stages of data reduction, data presentation, and conclusion. The research results show that PAI teachers at MI Fattahul Huda have implemented various digital strategies to strengthen religious moderation, including thematic YouTube videos, interactive quizzes using Quizizz and Kahoot!, student digital projects on tolerance themes, the development of digital teaching materials, and practices of digital religious literacy. Teachers also use moments of religious and national holidays as a means to strengthen peaceful and inclusive Islamic values. These strategies have proven to enhance students' active participation, reinforce the understanding of tolerance values, and cultivate a critical attitude towards religious content on social media. Thus, digital media can serve as an effective tool for instilling values of religious moderation in a contextual and in-depth manner from an early age.